Q: What is 6 squared plus 6 cubed - 3 cubed?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x(x2+5x+6)

x3 - 4x2 + x + 6 = (x + 1)(x - 2)(x - 3)

3 cube =27 4 cube =64 5 cube =125 6cube=216 so 3 cubed + 4 cubed + 5 cubed = 6 cubed

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

It is: 4+6^3 = 220

Related questions

y^3 + y^2 - 6 (y+2) (y-3) i think

Use a^3 + b^3 = (a + b)(a^2 - ab + b^2), where a^2 is a squared, a^3 is a cubed. Note that 216 = 6^3.

-6

x(x2+5x+6)

x3 - 4x2 + x + 6 = (x + 1)(x - 2)(x - 3)

(x - 3)(x^2 + 6)

3 cube =27 4 cube =64 5 cube =125 6cube=216 so 3 cubed + 4 cubed + 5 cubed = 6 cubed

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

6 squared is 36. 36 plus 3 is 39

2x(x^2+x-6)

(a - 2)(a^2 + 6)

It is: 4+6^3 = 220